Identifying consumer buying preferences of beef - Pieter Uys; Christo Bisschoff (Problems and Perspectives in Management, 2016)
This study investigated the drivers which influence consumers’ beef buying behavior. A validated questionnaire was used to collect the data and to evaluate consumer beef purchasing behavior. Exploratory factor analysis was employed to analyze the data while Cronbach alpha coefficient was used to calculate the reliability of the drivers. Satisfactory levels of reliability were recorded. The analysis identified eight drivers that influence the buying behavior of consumers when they purchase beef products. These drivers were: quality of the meat, buying preference, farming practices, intention to buy, health, convenience, packaging & presentation and future purchase. In addition, correlational analysis indicates that additional important attributes to buying behavior are supplier characteristics and packaging & presentation. The study culminates in a frame of reference for beef (and possibly other meat products) buying behavior analysis whilst it also provides a frame of reference for marketers to better understand their customers’ behavior when they are selling beef. As a result it is recommended that retailers focus their actions on the more important beef purchasing drivers and that the study be repeated on a larger scale so that the results of the present study can either be confirmed or further refined. Keywords: beef cattle, buying behavior, consumer preferences of beef, packaging, farming practices, factor analysis. JEL Classification: M30